Pengaruh Tax Avoidance dan Kinerja Keuangan Terhadap Nilai Perusahaan dengan Corporate Governance Sebagai Variabel Pemoderasi - Vina Astri Joharindu; Bintang Rajagukguk; Priyo Hari Adi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
This research aims to analyze the effect of tax avoidance, financial performance on firm value on firm value with corporate governance as a moderating variable.. The analysis technique used in this study is multiple linear regression to analyze our data statiscically. This study uses data obtained from the financial statements of manufacturing companies listed on the Indonesian Stock Exchange (IDX). Sampling using a purposive sampling method and obtained 135 samples. Based on the results of the analysis conducted shows that tax avoidance has a negative effect on the value of financial performance has a positive effect on firm value. Corporate governance strengthens the effect of tax avoidance on firm value and weakens the effect of financial performance on firm value.